KONSEP KELUARGA MUSLIM DALAM MENJAGA FITRAH SEKSUAL ANAK - Muhammad Rizki Febrian; Syafiq Riza Hasan (Al-Majaalis : Jurnal Dirasat Islamiyah, 2024)
Islam is a religion that runs according to human nature, so that it has mapped out the rules to fulfill human inner urges, including sexual desire, through the institution of marriage. Islam as a religion of nature is in harmony with the basic nature of humans. The purpose of this study is to dissect the concept of "sexual nature" and determine its parameters, how the concept of Muslim families in maintaining sexual nature and the analysis of cases of sexual deviation against the concept of Muslim families in maintaining sexual nature. The method in this study is qualitative non-interactive analytical concept. This study discusses sexual nature which is a tendency to follow Islamic rules in sexual life, because in Islam there is no monastic life, and at the same time Islam also prohibits the exposure of nudity and free sexual activities. There are stages in the concept of Muslim families in maintaining children's sexual nature, all of which require the role of parents, from age 0 until pre-marriage. These concepts are then linked to analyze cases of sexual deviation. It can be concluded that the factors involved in sexual deviation are not separated from the loss of parental roles in maintaining their children during their growth stages.   Keywords: deviation, sexual, maintenance. human nature.